Remark to the evaluation of the distribution norm of white noise - Kondratiev , Yu. G.; Streit , L. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The description of the space $(S)*$ of white noise distributions is received in the terms of the $S$-transform well-known in the white noise analysis.